Business success factors for microenterprises engaging in social commerce in Malaysia - Tan, Cin Cin (2023)
In Malaysia, online business has become integral in daily business operations. Social commerce is an emerging trend in the online business. Social commerce employs social media as a means of communication in facilitating the sale and purchase of goods and services. Entrepreneurs saw the potential of social media to increase sales, leading to an interest in social commerce. In addition, the rapid development of social media has also led to changes in the way entrepreneurs handle their daily operations. In promoting the growth of social commerce, government provided entrepreneurship programs for entrepreneurs, such as financial aid, advisory services, and training. Yet, business failure rate, particularly among microentrepreneurs, kept increasing. This suggested a lack of business elements that should have been prioritised by online businesses. Therefore, this study aimed to investigate the success factors of microenterprises that engaged in social commerce. A qualitative method was employed to ensure that robust data was collected and the research objectives were met. Purposive sampling was adopted in collecting the data. The analysis utilized thematic analysis to obtain insights into microenterprises and social commerce. The findings of this study demonstrated the success factors of microenterprises that were engaged in social commerce as part of their business expansion. The success factors framework was made up of seven important pillars: funding, financial management, marketing, management skills, technology, supplier management and government support. All these factors contributed to the microenterprises’ growth and sustainability. These factors were crucial to the success of microenterprises. They would have to be further examined and managed to ensure the microenterprises’ growth and long-term success. Microenterprises needed to prioritize each of these success factors and develop strategies to address them, especially in confronting and to flourish in Malaysia's highly competitive social commerce industry.